The international effect of economic crises on the volatility of futures prices and the volatility of underlying spot prices of stock indexes and commodities - Tham, Lucas Yew Jun (2022)
The recent 2 decades have seen more frequent high-volatility economic crises worldwide. A main question to be raised is whether these economic crises have an effect on the volatility of futures prices and the volatility of spot prices. This research also provides an opportunity to determine if there are any external factors that affect this relationship.